The Utilization of Learning Media in Fostering Student Learning Independence (Case Study at SMPN 1 and SMPN 8 Purwakarta) - Suharyanto Soro; Nana Herdiana Abdul Rahman; Heri Kusnandar; Eutik Suhendar (Civiliza Publishing, Indonesia., 2026)
Learning media is a form of technology that can be used as an intermediary to convey learning messages so that they can stimulate students' thoughts, feelings, attention, and interests. However, in practice, learning media is still not maximized in its function so that it does not clarify the presentation of the material, overcome the limitations of space and time, and increase the effectiveness of learning. This study aims to describe and analyze the role of the use of learning media in fostering student learning independence. The researcher uses a case study approach. Data was collected through observation, interviews, and documentation. The results of the study show that the use of visual, audiovisual, and information technology-based media contributes positively to increasing student initiative, responsibility, and activeness in learning. Learning media has been proven to help students understand the material independently and reduce dependence on teachers. The conclusion of the study is that the use of learning media can foster student learning independence.